Adhesion preference of the sticky bacterium Acinetobacter sp. Tol 5 - Yoshimoto, Shogo; Ishii, Satoshi; Kawashiri, Ayane; Matsushita, Taishi; Linke, Dirk; Göttig, Stephan; Kempf, Volkhard A. J.; Takai, Madoka; Hori, Katsutoshi (Frontiers in Bioengineering and Biotechnology, 2024)
Gram-negative bacterium Acinetobacter sp. Tol 5 exhibits high adhesiveness to various surfaces of general materials, from hydrophobic plastics to hydrophilic glass and metals, via AtaA, an Acinetobacter trimeric autotransporter adhesin (TAA).Although the adhesion of Tol 5 is nonspecific, Tol 5 cells may have prefer materials for adhesion. Here, we examined the adhesion of Tol 5 and other bacteria expressing different TAAs to various materials, including antiadhesive surfaces. The results highlighted the stickiness of Tol 5 through the action of AtaA, which enabled Tol 5 cells to adhere even to antiadhesive materials, including polytetrafluoroethylene with a low surface free energy, a hydrophilic polymer brush with steric hindrance, and mica with an ultrasmooth surface. Single-cell force spectroscopy as an atomic force microscopy technique revealed the strong cell adhesion force of Tol 5 to these antiadhesive materials. Nevertheless, Tol 5 cells showed a weak adhesion force toward a zwitterionic 2-methacryloyloxyethyl-phosphorylcholine (MPC) polymercoated surface. Dynamic flow chamber experiments revealed that Tol 5 cells, once attached to the MPC polymer-coated surface, were exfoliated by weak shear stress.The underlying adhesive mechanism was presumed to involve exchangeable, weakly bound water molecules. Our results will contribute to the understanding and control of cell adhesion of Tol 5 for immobilized bioprocess applications and other TAAexpressing pathogenic bacteria of medical importance.